2019
DOI: 10.1519/jsc.0000000000002561
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation of the Temporal Lobe Does Not Affect High-Intensity Work Capacity

Abstract: Stimulation of the left insular cortex may affect heart rate variability (HRV) and exercise effort perception. These studies investigated the effects transcranial direct current stimulation (tDCS) and electrode orientation on HRV and repeated maximal knee extensions. In study 1, following sham stimulation, anodal left temporal lobe stimulation, or anodal right temporal lobe stimulation, 10 male and 10 female subjects (age=21.0±1.5 yr) completed 50 maximum isokinetic extensions at 180°s. There was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 35 publications
1
41
0
11
Order By: Relevance
“…The left IC seems to have its activity diminished when high-intensity exercises are done, whereas exercises with higher sympathetic activity, characteristic in supramaximal exercises, increase the activity of right IC 34 . Furthermore, there is evidence that anodal tDCS applied over the left temporal cortex is not effective for high-intensity performance enhancement 35 . Accordingly, stimulating the left IC before a supramaximal intermittent cycling exercise does not modulate the pleasure and displeasure sensations, and consequently does not decrease the RPE response and performance improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The left IC seems to have its activity diminished when high-intensity exercises are done, whereas exercises with higher sympathetic activity, characteristic in supramaximal exercises, increase the activity of right IC 34 . Furthermore, there is evidence that anodal tDCS applied over the left temporal cortex is not effective for high-intensity performance enhancement 35 . Accordingly, stimulating the left IC before a supramaximal intermittent cycling exercise does not modulate the pleasure and displeasure sensations, and consequently does not decrease the RPE response and performance improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The IC is located below the temporal cortex and it is deeper than other cortical areas, such as the motor cortex. Although the subcortical areas are affected by tDCS 2,5 , stimulation of temporal lobe targeting IC is questionable 35 . However, other areas of the brain, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FT commenced with the same submaximal warm-up as the strength test (15 reps, concentric/concentric, 60 • /s) and consisted of 40 continuous concentric/concentric maximal contractions of the knee extensors and flexors at 120 • /s [25]. This FT protocol has been well established in both healthy people and people with neurological disorders [14,15,[26][27][28][29][30]. At minute 15 of the tDCS protocol (see "tDCS sessions" below), the R-FT was performed, followed by the L-FT.…”
Section: Isokinetic Fatigue Testingmentioning
confidence: 99%
“…(9) and CICCONE et al(34) that observed the increase of performance in healthy individuals when compared to Group sham.The literature has demonstrated that tDCS may modify the autonomic responses in healthy individuals Vandermeeren et al(35) and Clancy et al (36), in healthy athletes Montenegro et al (6) and Okano et al (9). This is the first study that has as purpose to assess the effects of tDCS over the left temporal lobe, in HRV in individuals with stroke sequel.…”
mentioning
confidence: 93%